A pressure–velocity jump approach for the CFD modelling of permeable surfaces. Issue 233 (February 2023) - Xu, Mao; Patruno, Luca; de Miranda, Stefano
Abstract: Permeable surfaces are extremely common in applications, ranging from wind shields installed on bridge decks to the outer layer of permeable double skin facades. However, due to the large scale separation between the overall dimensions of the structure and the size of the pores, their modelling in Computational Fluid Dynamics, CFD, simulations are still extremely problematic. In particular, explicitly modelling the pores geometry leads to prohibitive computational costs, while homogenized models based on the use of so-called pressure-jumps are often very crude simplifications of their aerodynamic behaviour. In this paper, a novel approach based on the use of pressure–velocity jumps, PVJ, is proposed. Firstly, the approach is deduced in a general form, based on mass and momentum conservation across the permeable surface. Then, some limit cases for which an analytical evaluation of the coefficients characterizing the model can be obtained are discussed. Finally, a ground mounted barrier is modelled, considering permeable surfaces of widely different aerodynamic behaviour. Results obtained modelling the barrier geometrical details and using the proposed PVJ approach are compared, confirming the soundness of the proposed approach. An OpenFOAM boundary condition implementing the proposed method is available at https://site.unibo.it/cwe-lamc/en . Highlights: A novel approach for the CFD modelling of permeable surfaces is proposed. The approach is based on pressure and tangential velocity jumps. The approach accounts for both normal and tangential forces. Results are compared to those obtained for the detailed permeable surface geometry.